If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(s + -2) = 2s Reorder the terms: -4(-2 + s) = 2s (-2 * -4 + s * -4) = 2s (8 + -4s) = 2s Solving 8 + -4s = 2s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-2s' to each side of the equation. 8 + -4s + -2s = 2s + -2s Combine like terms: -4s + -2s = -6s 8 + -6s = 2s + -2s Combine like terms: 2s + -2s = 0 8 + -6s = 0 Add '-8' to each side of the equation. 8 + -8 + -6s = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -6s = 0 + -8 -6s = 0 + -8 Combine like terms: 0 + -8 = -8 -6s = -8 Divide each side by '-6'. s = 1.333333333 Simplifying s = 1.333333333
| 9z-2(3z+8)=5 | | x/12=2/16 | | -15=k/12 | | f(x)inf(x)=-x | | x/12-2/16 | | -(2x+3)=6(2x-1) | | 2x=4/3-4 | | 5(3+k)=-40 | | -125+10h=230+7h | | ?525/ | | 3215479+93037364= | | -1/2n=6 | | 3(2w+4)=1 | | 2x-8x=16 | | 0=1.37x+1+x*x | | 5(x-2)-3x=3(x-5) | | 2*6/20 | | 6x+14=-7 | | 8x-2+3=8-4x | | 3/8=-1/8 | | 6/21=4/x | | 8m+2q*3m+4q= | | 6(2x-1)+4=5(3x-1) | | 1=(x-1)(x+1) | | Y(0)=4x+4 | | 7p-3=4p+9 | | 5*1.95= | | 8x+15=120 | | 3(2x-y)=ax-4 | | 8x+20=120 | | 400MG=0.4G | | X-2=35/2 |